1987
DOI: 10.1007/bf01880098
|View full text |Cite
|
Sign up to set email alerts
|

Stereoisomers and analogs of 14-methyl-1-octadecene, sex pheromone of peach leafminer moth,Lyonetia clerkella, L.

Abstract: The synthesis of the enantiomeric 14-methyl-1-octadecenes in >99% EE is described. Enantiomeric 2-methyl-1-hexanols were intermediates in the synthesis. The 1-alkene had been previously identified as the sex pheromone of the peach leafminer moth. Several closely related structures that have δ12 unsaturation are also described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Sugie et al first isolated (S)−14-methyl-1-octadecene (1) (Figure 1) as the sex pheromone of the peach leafminer moth, 2 and the synthesis of the racemic form of 1 was then achieved by a couple of teams. [3][4][5] It was revealed that the Sisomer was active through lure experiments on peach leafminer moths, while the Risomer was almost inactive. 6 Recently, Ando disclosed an informal synthesis of (±)−1, employing Schlosser's copper-catalyzed Grignard reaction.…”
mentioning
confidence: 99%
“…Sugie et al first isolated (S)−14-methyl-1-octadecene (1) (Figure 1) as the sex pheromone of the peach leafminer moth, 2 and the synthesis of the racemic form of 1 was then achieved by a couple of teams. [3][4][5] It was revealed that the Sisomer was active through lure experiments on peach leafminer moths, while the Risomer was almost inactive. 6 Recently, Ando disclosed an informal synthesis of (±)−1, employing Schlosser's copper-catalyzed Grignard reaction.…”
mentioning
confidence: 99%
“…This paper now describes the generation of optically pure 2-methylbutanoic acid (1), 2-methylpentanoic acid (2) 2-methylhexanoic acid (3), 2-ethylhexanoic acid (4), the corresponding alcohols 2-methyl-butan-l-01 (5), 2-methyl-pentan-I-ol (6), 2-methyl-hexan-I-ol (7), 2-ethyl-hexan-l-ol (8) and the esters etlJyl-2-methylbutanoate (9) and prenyl-2-methylpentanoate (10).…”
mentioning
confidence: 99%